On the Conceptual Model of Balanced Socio-Economic Development of the Arctic Territories - Anna I. Regeta; Kristina O. Malinina; Anton M. Maksimov (Arctic and North, 2022)
The article deals with the key aspects of the formation of the integrated socio-economic development of the Arctic zone of the Russian Federation (AZRF). The main purpose of the study is to create a conceptual model for balanced socio-economic development. The article uses such methods as comparison, analysis, deduction and induction. The importance of the development of these territories for the sustainable development of the country is shown. The main regulatory documents defining the development of this region are highlighted. Threats to the security of the Arctic zone of the Russian Federation are identified. The relations of other countries to the Arctic are considered. The importance of bringing the standard of living in the Arctic region closer to the average in Russia and the importance of this direction of action to reduce the negative demographic trend are outlined. Besides, the need to study the development of the Arctic region of the Russian Federation is determined not by statistical methods, but by new research methods. The importance of creating a megaproject for the development of the Arctic zone of the Russian Federation with specific measurable goals is highlighted. Such risks of this region are described as: population decline, in particular, the decline of the able-bodied population (including highly qualified personnel), the critical state of housing and communal services, the high cost of living and use of resources, the threat to environmental safety, weak diversification of production, long distances from industrial centers. Economic, social and environmental factors affecting the dynamics of the integrated socio-economic development of the Arctic region of the Russian Federation are considered. A conceptual model of balanced socio-economic development of the region was developed on the basis of a set of factors. The conceptual model of integrated development of the Arctic regions of the Russian Federation is a complex of various factors. This model can become a basis for the preparation ...